Gaya Bahasa Kiasan dalam Novel Rasa Karya Tere Liye dan Implikasinya terhadap Pembelajaran Teks Novel - Mutiara Khairani; Zulfikarni Zulfikarni (Universitas Katolik Widya Karya Malang, 2023)
This research text the novel Rasa by Tere Liye as the basic reference of the research. The problems studied in this study are related to the figurative language style found in the novel Rasa by Tere Liye. This study aims to (1) describes the style of figurative language contained in the novel Rasa by Tere Liye and (2) describe the implicit figurative language style in Tere Liye's novel Rasa towards novel learning texts in senior high schools. The method used in this research is descriptive qualitative method through content analysis approach. The resulting data is in the form of words in quotations. The data found in this study are in the form of phrases, clauses and sentences that contain elements of figurative language in the novel Rasa by Tere Liye. The author's most dominant style of language used is personification of 25 quotations. The results of the analysis of figurative language style are implied in learning Indonesian in the 2013 curriculum in senior high schools